A prospective observational study of maternal and perinatal outcome in previous one lower segment caesarean section in District Hospital, Karnataka - Amreen, Syeda Atufiyat; Rathod, Lakshman; Rathod, Anil Kumar; Gupta, Namita; Bijapure, Hidaytullah R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Lower segment caesarean section (LSCS) is defined as extraction of baby through an incision made in lower segment through trans peritoneal approach. CS is performed only when circumstances demand it, as it is not a simple procedure and may be associated with various complications. It has been found that maternal mortality associated with CS can be three times that of normal vaginal delivery. Methods: A prospective observational study which considered pregnant women admitted in MCH, District Hospital, Vijayapura who underwent one LSCS who were further assessed by taking history and clinical examination. Maternal and perinatal outcomes were observed. Results: A total of 150 pregnant women were taken into study who came for admission in District Hospital for further management. Maternal and perinatal outcomes were considered in the study. Of the pregnant women who had repeat caesarean deliveries, 68.7% had emergency deliveries (51.5%) and elective caesarean deliveries (48.5%). Of these, the majority (54.7%) had no intraoperative problems, while 14.6% developed adhesions. Additionally, 52% of babies were born weighing between 2.5 and 3 kg, and 78% of them showed no symptoms. Conclusions: The prevalence of CS has increased in recent years due to the development of new methods for assessing fetal well-being. However, it’s important to carefully consider the decision to perform a primary CS, as there is always a risk of uterine scar rupture in future pregnancies if a vaginal birth is attempted after a previous caesarean.